(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Aconitum heterophyllum, commonly known as aruna, belongs to the Ranunculaceae family and is used in Ayurvedic formulations to treat diarrhoea, liver difficulties, and other ailments. Alkaloids, proteins, carbohydrates, saponins, amino acids, quinones, flavonoids, glycosides, terpenoids, and other phytochemicals are found in this plant. Not only are the different medicinal characteristics of this plant mentioned in this study, but the profile of its toxicological experiments conducted on rats is also examined. Unlike other Aconitum species, Aconitum heterophyllum was proved to be helpful in a rat poisoning study. To begin, the plant’s ethanolic extract was tested for oral toxicity, but it was found to be harmless. Castor oil’s action was reversed by an ethanolicextract of the plant. Furthermore, this plant possesses antibacterial properties. After summarizing all of this plant’s medicinal characteristics, it might prove to be a great source of information for academics, traditional medicine practitioners, and the pharmaceutical business.